An analysis of how hijabi youth experience social activities in Ottawa secondary schools - Alvi, Saba (University of Ottawa (Canada), 2008)
This interpretive qualitative study explores the lived experiences of seven hijabi youth and how they experience social activities offered in their secondary schools in Ottawa, Ontario. The main research questions are: (1) How do hijabi women in Ottawa secondary schools experience the social activities offered by their schools, and (2) In what ways are hijabi girls being included or excluded from social activities because of their religious obligations? A phenomenological tradition of inquiry has been used in order to understand the essence of the experience as perceived by each participant. Analysis has been conducted using Moustakas' (1994) modifications to the Stevick-Colaizzi-Keen Method of Phenomenological Data. The researcher has also shared her own story of interaction with social activities in high school. The findings and implications of this study have been categorized into themes in order to illustrate the essence of how hijabi youth experience social activities in Ottawa secondary schools. The themes identified are: (a) Us Versus Them; (b) Fighting Stereotypes; (c) Culture Differences; and (d) A Desire to Participate. The first emergent theme, Us Versus Them, explains the alienation hijabi students feel when partaking in social activities offered at their schools. The second emergent theme, Fighting Stereotypes, details the everyday questions, assumptions and judgements hijabi students face from peers both Muslim and non-Muslims that ultimately discourage them from partaking in activities. The third emergent theme, Culture Differences, explains how current social activities in schools compromise the religious values of hijabi girls. The fourth and final emergent theme, A Desire to Participate illustrates participants' willingness and in some instances, eagerness to participate in school social activities. The author aims to raise awareness of how hijabi girls experience social aspects of high school and with that, a message for academic authorities to examine how their students are being included or excluded with means towards creating in inclusive environment. The conclusion of this thesis raises implications for further study such as the role that self-esteem plays in the participation of hijabi girls in school social activities.
Keywords: Education, Bilingual and Multicultural.; Education, Sociology of.